2021
DOI: 10.4149/neo_2020_200614n629
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CDC20 suppressed cell proliferation, induced apoptosis, triggered cell cycle arrest in osteosarcoma cells, and enhanced chemosensitivity to cisplatin

Abstract: Osteosarcoma (OS) is a common malignant bone tumor that occurs in adolescents or children under the age of 20, which is extremely difficult to cure and has a high recurrence rate. Recent studies showed that cell division cycle 20 (CDC20) overexpression is associated wit h poor prognosis in patients with osteosarcoma. However, the function of CDC20 in osteosarcoma has not been investigated clearly. In this study, we aim to explore the role of CDC20 in two independent human py sensitivity. We applied multiple ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Our results demonstrated that candidate loci can be analyzed in future studies of folliculogenesis. Typically, CCNA1 59 , CDC20 60 , and CPEB1 61 (which are cell cycle regulators) and BRDT 62 and FBXO43 63 (which are involved in cell meiosis) showed more PEIs and contacted with SEs during the SWF stage, though these interactions and active enhancers decreased in later stages (Supplementary Fig. 12a–e ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrated that candidate loci can be analyzed in future studies of folliculogenesis. Typically, CCNA1 59 , CDC20 60 , and CPEB1 61 (which are cell cycle regulators) and BRDT 62 and FBXO43 63 (which are involved in cell meiosis) showed more PEIs and contacted with SEs during the SWF stage, though these interactions and active enhancers decreased in later stages (Supplementary Fig. 12a–e ).…”
Section: Resultsmentioning
confidence: 99%
“…The tumor-related phenotypes observed locally in PVNS tissues mainly include increased cell proliferation and migration. Cell division cycle protein 20 ( 26 ), cyclin-dependent kinase subunit 2 ( 27 ), and E2F transcription factor 2 ( 28 ) were reported to be closely associated with cell proliferation and cell cycle. In addition, coactosin-like F-actin binding protein 1 ( 29 ), Rac family small GTPase 2, and RAC1 guanine nucleotide exchange factor mediated cytoskeleton assembly and chemotaxis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there is different evidence which suggest that CDC20 contributes to a number of cellular processes that have been partially explored. An overexpression and/or oncogenic role of CDC20 has been already described in a variety of human solid tumors [ 9 , 10 ] including pancreas [ 11 , 12 ], breast [ 13 , 14 ], lung [ 15 , 16 ], prostate [ 17 19 ], gastric, colorectal [ 16 , 18 ], hepatocellular [ 20 , 21 ], kidney [ 22 ], ovarian cancer [ 23 , 24 ], osteosarcoma [ 25 27 ] and glioblastoma [ 28 , 29 ]. Moreover, CDC20 expression level has been reported as a putative marker of clinical outcome in many cancer types, being associated with advanced stage, high grade and poor prognosis [ 9 , 10 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%